Research Progress and Applications of 2D Antimonene - Tingting Zhong; Lina Zeng; Zaijin Li; Li Sun; Zhongliang Qiao; Yi Qu; Guojun Liu; Lin Li (Applied Sciences, 2022)
Antimonene has attracted much attention due to its excellent properties such as high carrier mobility, excellent thermoelectric performance and high stability. In order to verify its theoretical advantages, a large number of experimental studies have been carried out and its applications explored. This paper mainly introduces the experimental preparation of antimonene by mechanical exfoliation, liquid phase exfoliation and epitaxial growth, summarizes the advantages and disadvantages of each method, and describes the applications of antimonene in sensor, battery, medicine and laser. Finally, prospects have been made to the future applications of antimonene in photoelectric field.